The Effect of Competence, Motivation, Leadership, Work Environment, and Compensation On Employee Performance at SSC Nails Salon - Fressia Serliana; Andika Prasetya Nugraha; Netti Syafitri (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
This study examines the effect of competence, motivation, leadership, work environment, and compensation on employee performance at SSC Nails Salon. The research was conducted using a quantitative approach with primary data collected through questionnaires distributed to all 30 employees. A census sampling technique was applied due to the relatively small population size, ensuring that the sample fully represented the workforce of the salon. Data analysis was performed using multiple linear regression with SPSS 26.0, supported by validity and reliability testing, classical assumption tests, partial hypothesis testing (t-test), simultaneous hypothesis testing (F-test), and the coefficient of determination (R²). The results of the partial tests indicate that competence, motivation, leadership, work environment, and compensation each have a statistically significant effect on employee performance, with significance values below the 0.05 threshold. The simultaneous F-test also confirms that all independent variables collectively influence employee performance, demonstrating that employee performance is shaped by an integrated combination of individual capability, psychological encouragement, managerial direction, workplace conditions, and reward systems. Furthermore, the coefficient of determination reveals that the regression model explains 94.5% of the variance in employee performance, indicating very strong explanatory power and model stability. These findings suggest that improving employee performance at SSC Nails Salon requires a comprehensive human resource management strategy that emphasizes competency development, motivational reinforcement, effective leadership practices, supportive work environments, and equitable compensation policies. This study contributes novelty by providing empirical evidence of employee performance determinants within the beauty service industry, particularly in a nail salon context, which remains limited in previous performance research.